1994
DOI: 10.1128/jb.176.16.4985-4992.1994
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation and dephosphorylation of the NarQ, NarX, and NarL proteins of the nitrate-dependent two-component regulatory system of Escherichia coli

Abstract: The NarX, NarQ, and NarL proteins make up a nitrate-responsive regulatory system responsible for control of the anaerobic respiratory pathway genes in Escherichia coli, including nitrate reductase (narGIJI), dimethyl sulfoxide/trimethylamine-N-oxide reductase (dnsABC), and fumarate reductase (frdABCD) operons among others. The two membrane-bound proteins NarX and NarQ can independently sense the presence of nitrate and transfer this signal to the DNA-binding regulatory protein NarL, which controls gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
98
0
1

Year Published

1995
1995
1998
1998

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(108 citation statements)
references
References 39 publications
9
98
0
1
Order By: Relevance
“…Therefore, NarX and NarQ are equally effective in sensing the presence of nitrate and relaying this signal to the regulator components of the pathway, a finding which has been extensively studied for other nitrate-responsive operons (21,28,33). Either of the response regulators, NarL or NarP, was sufficient to confer maximal nitrate and nitrite repression in rich medium, while the NarL protein appeared to be marginally more effective when cells were grown in minimal medium.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Therefore, NarX and NarQ are equally effective in sensing the presence of nitrate and relaying this signal to the regulator components of the pathway, a finding which has been extensively studied for other nitrate-responsive operons (21,28,33). Either of the response regulators, NarL or NarP, was sufficient to confer maximal nitrate and nitrite repression in rich medium, while the NarL protein appeared to be marginally more effective when cells were grown in minimal medium.…”
Section: Discussionmentioning
confidence: 95%
“…3, lane 3). It has been demonstrated that incubation of the NarL protein with acetyl phosphate results in the transfer of the phosphate group to the protein (28).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gel Electrophoresis-Protein samples were prepared in 2.5% SDS, 5% ␤-mercaptoethanol, and 0.005% bromphenol blue as described (17). After heating for 5 min at 90°C, 1 l of the sample was applied to a 12.5% homogenous polyacrylamide SDS gel (Phastsystem, Pharmacia).…”
Section: Methodsmentioning
confidence: 99%